Molecular Biodiversity Inventory of the Ichthyofauna of the Czech Republic - Mendel, Jan; Marešová, Eva; Papoušek, Ivo; Halačka, Karel; Vetešník, Lukáš; Šanda, Radek; Koníčková, Milena; Urbánková, Soňa (IntechOpen, 2012)
None